2019
DOI: 10.1002/jmr.2829
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interaction between split aptamer and vascular endothelial growth factor 165 using single molecule force spectroscopy

Abstract: Understanding the binding of split aptamer/its target could become a breakthrough in the application of split aptamer. Herein, vascular endothelial growth factor (VEGF), a major biomarker of human diseases, was used as a model, and its interaction with split aptamer was explored with single molecule force spectroscopy (SMFS). SMFS demonstrated that the interaction force of split aptamer/VEGF165 was 169.44 ± 6.59 pN at the loading rate of 35.2 nN/s, and the binding probability of split aptamer/VEGF165 was depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Since the binding mechanism between the intact aptamers and Myo has not been clarified, the intact aptamer against Myo was first randomly divided at different sites into split aptamer 1 and split aptamer 2, as shown in Scheme . Then, split aptamer 1 and split aptamer 2 were attached to the AFM tip and gold substrate, respectively. , Next, AFM measurements were carried out in the absence or presence of Myo . Given that there was a significant difference in the binding probability with or without the target, it was speculated that the binding probability may be one of the judgment parameters for engineering split aptamer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the binding mechanism between the intact aptamers and Myo has not been clarified, the intact aptamer against Myo was first randomly divided at different sites into split aptamer 1 and split aptamer 2, as shown in Scheme . Then, split aptamer 1 and split aptamer 2 were attached to the AFM tip and gold substrate, respectively. , Next, AFM measurements were carried out in the absence or presence of Myo . Given that there was a significant difference in the binding probability with or without the target, it was speculated that the binding probability may be one of the judgment parameters for engineering split aptamer.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Next, AFM measurements were carried out in the absence or presence of Myo. 29 Given that there was a significant difference in the binding probability with or without the target, it was speculated that the binding probability may be one of the judgment parameters for engineering split aptamer. That is, if the binding probability was high, it was suggested that the split aptamers could bind to the target.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The force measurements between Apt1- or Apt2-functionalized tips and Aβ 40 -aggregate-modified Au substrates were conducted at a loading rate of 3.52 × 10 4 pN/s by JPK biological AFM (JPK Instruments AG, Germany), which were shown in Figure A. Herein, the utility of PEG 3400 linker could raise the steric flexibility and separate different dissociation events. , Further, in order to obtain a single dissociation event, several experiment conditions, including immobilization density of Apts and Aβ 40 aggregates, were optimized. , Simultaneously, a series of control groups were performed to distinguish between specific and nonspecific interactions. As shown in Figure B, the specific peak would vanish when Apts-functionalized AFM tips were blocked with Aβ 40 aggregates or the Aβ 40 -aggregate-modified Au substrates were blocked with Apts.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, the utility of PEG 3400 linker could raise the steric flexibility and separate different dissociation events. 29,30 Further, in order to obtain a single dissociation event, several experiment conditions, including immobilization density of Apts and Aβ 40 aggregates, were optimized. 31,32 Simultaneously, a series of control groups were performed to distinguish between specific and nonspecific interactions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%